Uma análise da ascensão chinesa a partir da Teoria do Imperialismo - Costa, Simone Kawakami Gonçalves [UNESP] (2015)
China's rise to the role of economic power of global significance was established as one of the most significant changes to the interstate relations that occurred at the turn of the twentieth century to the twenty-first century. The chinese development raised among many authors hypothesized that China would be advancing to raise to the hegemonic power condition, occupying the place that once belonged to the United States. Based on this background, this research seeks to conduct a study on the peculiar history of the country from the 1949 revolution, when it establishes the People's Republic of China, and the rapprochement with the United States at the expense of the one who should be your ally natural, the Soviet Union. It is also discussed the process of economic, political and social of the country, from the reforms adopted by Deng Xiaoping, and later of the capital injection in the form of foreign investment law, one of the elements responsible for China's rise. This discussion is intended to provide some necessary elements to draw assumptions about what kind of state China was shaping up, its place in international relations, from the analytical elements in the classical theory of imperialism as defined by Vladimir Lenin, to discuss the landmark of contemporary hegemonic transition and the present capitalist crisis.